Sources of resilience in adolescent female Rohingya survivors stranded in Aceh - Fadhilah, Cut Rafyqa; Lubis, Indah Sari Liza; Nisfiary, Reny Khaerany; Sarah, Cut (INSPIRA: Indonesian Journal of Psychological Research, 2023)
In 2015 to 2016 when the Rohingya were stranded in Kuala Langsa Harbor, Aceh. The research was conducted when the Rohingya survivors had been living in Aceh for six months. For most people, entering puberty is not easy. Adolescence is a stormy and stressful time because it is a time of emotional turmoil and imbalance. For Rohingya adolescents who experienced this runaway tragedy, of course, the adolescent phase they went through adds color, uniqueness, difficulties, and pressures that are different from ordinary adolescents who did not go through a tragedy in their lives. These conditions make Rohingya adolescents have to survive and find their ways to get through this tragedy. This research aims to discover the sources of resilience owned by adolescent girls who are Rohingya survivors. It is known from previous research that adolescent girls are not as resilient as adolescent boys and tend to be more sensitive and stressed when facing complex and stressful situations. This study uses a qualitative method with a phenomenological approach. The subject was taken by purposive sampling and amounted to only one person who was 16 years old. Resilient sources obtained by Rohingya adolescent survivors stranded in Aceh are obtained from internal sources, namely, I Am and I Can. External sources, namely, I have external support and sources in increasing resilience that are received from social support and trades.